Substantiation of the technology of mineral extraction from the bottom of the continental shelf with an autonomous underwater vehicle - Victor Evgenyevich Kislyakov; Pavel Viktorovich Katyshev; Yaroslav Evgen`evich Linkov; Alexandra Vadimovna Sharova; Anna Nikolaevna Lopatina; Aleksandr K Kirsanov (Brawijaya University, 2023)
The extraction of mineral resources from the bottom of the continental shelf is presently becoming very promising in terms of their current depletion on the continents. However, the development of the mineral resource base of the world ocean requires the creation of specialized equipment and technological schemes for its use. Such equipment should ensure safe, environmentally friendly, trouble-free operation in difficult hydrosphere conditions. One of the innovative ways of such development is the use of autonomous mining vehicles. The most energy-consuming part of the work of these vehicles is the process of lifting the loaded vehicle to the surface. This article discusses the optimization of energy costs for lifting an autonomous mining vehicle from the bottom of the continental shelf with the use of gases formed during the detonation of explosives.